2018
DOI: 10.1108/srj-10-2017-0204
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and corporate social responsibility practices: evidence from an emerging economy

Abstract: Purpose The purpose of this study is to present and test a conceptual framework that describes the Islamic religiosity parameters of riba, zakat and mafsadah and their influence on the adoption of firms’ corporate social responsibility (CSR) practices. Design/methodology/approach The study applied structural equation modelling to empirically test the proposed model on a sample of 109 Pakistan Stock Exchange (PSX) listed firms. Findings The study finds that the Islamic religiosity parameters of riba and maf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 142 publications
(224 reference statements)
4
30
0
6
Order By: Relevance
“…Religion is a significant part of how many Muslims experience their lives, including their behaviors and work practices (Ali, 1992;Hodge, 2002;Khan, Abbas, Gul, & Raja, 2015). The pillar of Zakat in Islamic faith in particular motivates Muslims to take a proactive approach to pinpointing and improving problematic situations (Zaman et al, 2018). At the same time, Muslims exhibit clear variations in the extent to which their religious beliefs inform their work activities (Ali, 2005;Murtaza et al, 2016).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Religion is a significant part of how many Muslims experience their lives, including their behaviors and work practices (Ali, 1992;Hodge, 2002;Khan, Abbas, Gul, & Raja, 2015). The pillar of Zakat in Islamic faith in particular motivates Muslims to take a proactive approach to pinpointing and improving problematic situations (Zaman et al, 2018). At the same time, Muslims exhibit clear variations in the extent to which their religious beliefs inform their work activities (Ali, 2005;Murtaza et al, 2016).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…This religion strongly encourages employees to take the initiative in contributing voluntarily to their organization's well-being (Alhyasat, 2012;Murtaza et al, 2016), including by identifying innovative solutions to organizational problems (Kumar & Che Rose, 2010). Religiosity might generate a tendency toward conformism in general (Saroglou, Corneille, & Van Cappellen, 2009), but the principles underlying Islamic faith-and particularly the notion of Zakat, one of the five pillars of the Islamic code of life, which requires people to be proactive in alleviating adverse situations (Olanipekun, Brimah, & Sanusi, 2015;Zaman, Roudaki, & Nadeem, 2018)support the notion that employees should do their utmost to change and improve the organizational status quo, even if these efforts are not included in formal job descriptions.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other DCSR scholars like Zaman et al. (2018, p. 368) studied how religion shapes CSR outcomes in developing contexts and revealed that “better religious firms seem to place more emphasis on social responsibility obligations.” This “(I5) Insensitivity” also occurred in the form of expectations being placed on businesses to engage in refugee crisis relief efforts. All refugee relief efforts are noble and much‐needed, however, the discourse was framed around the company’s commercial interests with little regard for the traumatic circumstances that refugees find themselves in.…”
Section: Results: Diagnostic Presentation and Discussionmentioning
confidence: 97%
“…Apart from the moderating influence, proposed here, of customer characteristics, there are other possible moderating effects. For instance, religiosity plays a significant role in the relationship between service recovery and recovery satisfaction (Rashid & Ahmad, 2014 ) and firm’s religiosity influences on corporate social responsibility practices (Zaman et al, 2018 ). The authors suggest focusing on the direct relationship between customer characteristics and other dependent variables — for example, between customer efforts in value-creation activities and behavioral intentions and quality of life (Sweeney et al, 2015 ) and between customer religiosity and behavioral patterns in the marketplace (Muhamad & Mizerski, 2007 ).…”
Section: Discussionmentioning
confidence: 99%